2019
DOI: 10.1371/journal.pone.0213657
|View full text |Cite
|
Sign up to set email alerts
|

Handwriting movements for assessment of motor symptoms in schizophrenia spectrum disorders and bipolar disorder

Abstract: The main aim of the present study was to explore the value of several measures of handwriting in the study of motor abnormalities in patients with bipolar or psychotic disorders. 54 adult participants with a schizophrenia spectrum disorder or bipolar disorder and 44 matched healthy controls, participated in the study. Participants were asked to copy a handwriting pattern consisting of four loops, with an inking pen on a digitizing tablet. We collected a number of classical, non-linear and geometrical measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 82 publications
(84 reference statements)
1
8
0
Order By: Relevance
“…In a more recent paper, Crespo et al investigated the use of handwriting in the study of motor abnormalities in patients suffering from bipolar or psychotic disorders. Outcomes demonstrated that individuals affected by schizophrenia spectrum disorder or bipolar disorder manifested significant motor impairments [65]. The handwriting of patients was distinguished by a significant decrease in velocity and acceleration and an increase in the length, disfluency and pressure with respect to controls.…”
Section: Methodologies and Applicationsmentioning
confidence: 99%
“…In a more recent paper, Crespo et al investigated the use of handwriting in the study of motor abnormalities in patients suffering from bipolar or psychotic disorders. Outcomes demonstrated that individuals affected by schizophrenia spectrum disorder or bipolar disorder manifested significant motor impairments [65]. The handwriting of patients was distinguished by a significant decrease in velocity and acceleration and an increase in the length, disfluency and pressure with respect to controls.…”
Section: Methodologies and Applicationsmentioning
confidence: 99%
“…Bolbecker et al [28] reported balance impairments in euthymic individuals with bipolar disorder during a static task, while Kang et al [29] reported impaired balance in depressed but not euthymic individuals with bipolar disorder during a dynamic task. Dyskinesia has also been reported in bipolar disorder [30,31], including one study of euthymic individuals [32], as has Parkinsonism [30].…”
Section: Introductionmentioning
confidence: 95%
“…This kind of task is especially challenging for those people affected by cognitive impairment, such as dementia, mild cognitive impairment, etc. This is the case of the house drawing Archimedean spiral, meanders and straight lines -Parkinson's disease [86,85] -Huntington's disease [7] -essential tremor [63,80,70,27] -developmental dysgraphia [31] -fatigue [34] -brachial dystonia [81] Single or overlapped circles -Huntington's disease [7] -schizophrenia [9] Spring task -fatigue [34] -developmental dysgraphia [31,103] -schizophrenia [9,14] -bipolar disorder [14] -Parkinson's disease [93] -Huntington's disease [7] Rainbow task -developmental dysgraphia [31,67] Saw task -developmental dysgraphia [31] Drawing Tasks Security (user identification and verification)…”
Section: Tasks Classificationmentioning
confidence: 99%